Breeding population of Peregrine Falcon (Falco peregrinus) in Lazio, Central Italy: 1983–2017 - Brunelli, Massimo; Sarrocco, Stefano (Ornis Hungarica, 2018)
In 1983–1984 the nesting population of Peregrine Falcon (Falco peregrinus) in Lazio was estimated to 25–30 pairs located mainly in the limestone massifs of the Southern Anti-Apennines and the Ponziane Islands. The monitoring carried out in the following years showed a steady increase in population size and range. In 2014–2017, the breeding population was 166–193 pairs distributed over most of the regional territory. In four regional macro-geographic areas characterized by different morphologies, lithological and landscape typologies, the density was calculated by NND method, which varied from a minimum of 0.90 to a maximum of 1.77 pairs/100 km2; average distance between sites from 3848.18 m to 6526.87 m. The urban population of Rome increased from the first nest found in 2001 to 15 currently breeding pairs; the first artificial nest was discovered in 2001 on the building, currently 14 are known. At present in Lazio 16 nests are located in quarries. In the years 2008, 2014, 2015 and 2016, the fledging rate registered was 2.26 (SD = 0.94; bp = 153).